Pancasila Student Profile Dimensions of Critical Reasoning through Differentiation Learning in the Context of Independent Learning - Hardiany, Desi; Rif'at, Mohamad; Siregar, Nurfadilah; Jamiah, Yulis; Hartoyo, Agung (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This research aims to describe a study of the profile of Pancasila students who reason critically through differentiated learning on circle material in class VIII of SMP Negeri 9 Simpang Hilir. The method used is qualitative research in descriptive form, involving class VIII A students. Data was collected through observation, questionnaires and tests. The results of the research show that the results of the learning style test of class VIII A students before differentiated learning show a diversity of students' learning style preferences: 10 people are kinesthetic, 3 people are auditory, and 7 people have a combination of two learning styles, namely 1 visual kinesthetic, 3 visual kinesthetic, 2 visual auditory, and 1 auditory visual. Preliminary test results show that the average critical reasoning ability score of class VIII A students is 57.6, which is in the "low" category. Of the 26 students, 6 had scores in the "medium" category, and 10 others were in the "low" category. There is a relationship between learning styles and critical reasoning abilities in assessing students' initial knowledge. The average score of students' LKPD at the second meeting was lower because the questions emphasized applications with high critical reasoning indicators. Differentiated learning has been proven to be effective in improving critical reasoning abilities, both in the medium and low groups. From the self-assessment questionnaire, 7 students were in the "Very Good" category and 13 students were "Good", in differentiated mathematics learning in circle material. There is a positive relationship between the results of students' critical reasoning self-assessment questionnaires and the results of the final learning assessment. Thus, differentiated learning has proven to be effective in implementing the Pancasila student profile of critical reasoning and improving student learning outcomes in circle material in class VIII.